EU India relations: a critique - Wulbers, Shazia Aziz (ed.) (New Delhi, 2008)
This chapter examines the way the EU, which in official documents designates 'strategic partner' India as a 'natural' and 'equal' partner, addresses development challenges in India. The first section looks at the EU's organisational coherence for its development cooperation with India, while subsequent sections respectively examine shifts in development cooperation, before looking at the two-pronged approach to development chosen by the EU to answer to the realities of the two worlds coexisting in India. The concluding sections argue that while the EU is still strongly committed towards fighting against poverty in India via its development cooperation, its strategic interests in making India a partner on the world stage, coupled with India's desire to access EU's markets, prematurely diverts development cooperation efforts and resources towards trade and economic cooperation.
Keywords: India-foreign economic relations-Europe